Determination of rice (Oryza sativa L.) site suitability using multi-criteria decision-making based on the best-worst method. Issue 27 (13th December 2022) - Tercan, Emre; Dengiz, Orhan
Abstract: The goal of this study was to identify the best convenient fields for rice ( Oryza sativa L.) production utilizing BWM-GIS integration based on some physico-chemical and productivity properties of the soils formed on Çarşamba Plain. Nine soil quality parameters rest on the crucial predictor variables defining rice yield were subsumed into RSI model. Exponential semivariogram model of OK was determined as the lowest RMSE value (0.7290) to generate distribution map. According to result map, it was found that the greatest RSI value was in Vertisol soils and the lowest RSI value was in Entisol soils. In addition, although high clay content, the soils classified as Typic Calciustert were put among low RSI classes in quality assessment because of their high slope. The bio-physical plans and land suitability analyses for rice cultivation can assist the conserving of the environment and to aid for decision makers considering future land use policy.